Secukinumab is superior to ustekinumab in clearing skin of subjects with moderate to severe plaque psoriasis: CLEAR, a randomized controlled trial - Thaçi, Diamant; Blauvelt, Andrew; Reich, Kristian; Tsai, Tsen-Fang; Vanaclocha, Francisco; Kingo, Külli; Ziv, Michael; Pinter, Andreas; Hugot, Sophie; You, Ruquan; Milutinovic, Marina (Journal of the American Academy of Dermatology, 2015)
Secukinumab, a fully human anti-interleukin-17A monoclonal antibody, has shown superior efficacy to etanercept with similar safety in moderate to severe plaque psoriasis (FIXTURE study). We sought to directly compare efficacy and safety of secukinumab versus ustekinumab. In this 52-week, double-blind study (NCT02074982), 676 subjects were randomized 1:1 to subcutaneous injection of secukinumab 300 mg or ustekinumab per label. Primary end point was 90% or more improvement from baseline Psoriasis Area and Severity Index (PASI) score (PASI 90) at week 16. Secukinumab (79.0%) was superior to ustekinumab (57.6%) as assessed by PASI 90 response at week 16 (P < .0001). The 100% improvement from baseline PASI score at week 16 was also significantly greater with secukinumab (44.3%) than ustekinumab (28.4%) (P < .0001). The 75% or more improvement from baseline PASI score at week 4 was superior for secukinumab (50.0%) versus ustekinumab (20.6%) (P < .0001). Percentage of subjects with the Dermatology Life Quality Index score 0/1 (week 16) was significantly higher with secukinumab (71.9%) than ustekinumab (57.4%) (P < .0001). The safety profile of secukinumab was comparable with ustekinumab and consistent with pivotal phase III secukinumab studies. The study was not placebo-controlled and of short-term duration. Secukinumab is superior to ustekinumab in clearing skin of subjects with moderate to severe psoriasis and improving health-related quality of life with a comparable safety profile over 16 weeks.